Overwinter shifts in the feeding ecology of juvenile Chinook salmon. (20th August 2016) - Hertz, Eric; Trudel, Marc; Tucker, Strahan; Beacham, Terry D.; Mazumder, Asit
Abstract : Winter is thought to be a critical period for many fish in the ocean, but their ecology during this time tends to be poorly understood. We quantified the feeding ecology of juvenile Chinook salmon ( Oncorhynchus tshawytscha ) off the west coast of Vancouver Island in British Columbia, Canada, in autumn and winter to determine how seasonality could affect diet. Using stomach contents and stable isotopes, we tested the hypothesis that the winter diet of juvenile Chinook salmon differs from that of the autumn diet. Stomach-content data showed a shift from a primary reliance on amphipods in autumn to euphausiids in winter. This finding was generally corroborated by the stable isotope analysis, although mixing models suggested a greater contribution of fish prey to the diet in both autumn and winter. Understanding the diet of fish during winter may provide useful information for management as a first step in understanding the factors influencing mortality across life stages.